An analysis of supply chain collaboration index by using FAHP and SCCI: a case study of organic fertiliser company X, Indonesia. Issue 1 (November 2021) - Dania, W A P; Hidayat, A; Nugraha, B A; Lestari, E
Abstract: Supply chain collaboration is one of the most crucial variables of driving business success in organic fertiliser Companies, especially to maintain the continual flow from upstream to downstream. Therefore, understanding the level of collaboration factors is vital in sustaining the partnership as well as reducing any conflicts among stakeholders. This study aims to measure the depth of collaboration among Company X and its suppliers. The assessment of the supply chain collaboration index will perform Fuzzy Analytical Hierarchy Process (FAHP) to weight the collaboration behaviour factors and Supply Chain Collaboration Index (SCCI) to measure the depth level of collaboration. The collaboration behaviour factors examined in this study are including joint effort, collaboration values, sharing activities, adaptation, trust, power, stability, commitment, continuous improvement and coordination. Based on the computation process using SCCI, the collaboration index among company X and its supplier is 76.72 on a scale of 1-100. It implies that the collaboration is at a moderate level. Consequently, the company needs to recognise the low score factors and develop a strategy for improvement. Some aspects that deserve further attention are sharing activities, power, and stability. By enhancing the performance of these factors, the supply chain collaboration index can also be increased.